Assessment of Pollen Viability, Germination, and Tube Growth in Eight Tunisian Caprifig (Ficus carica L.) Cultivars. (27th June 2013) - Gaaliche, Badii; Majdoub, Afifa; Trad, Mehdi; Mars, Messaoud
Abstract : The evaluation of pollen viability and its germination capacity are two essential criteria for pollinator's characterization. This study was carried out to evaluate pollen quality of eight caprifigs grown in the center-east and north-west of Tunisia. Two colorimetric tests 2, 3, 5-triphenyl tetrazolium chloride (TTC) and acetocarmine were used to estimate pollen viability. Germination rate and pollen tube growth in a culture medium containing 5% sucrose, 5 ppm boric acid (H3 BO3 ) and 1% agar were registered after 24, 48, and 72 hours (H) of incubation. Results showed that the highest pollen viability rate (84%) was obtained by TTC test in caprifig Assafri, followed by Jrani (80.2%), Djebba 2 (77.8%), and Djebba 1 (73.6%). That of other caprifigs did not exceed 50% for the two tests. In all caprifig types, germination rate and pollen tube growth varied according to the incubation period. The highest percentage of germination (72%) and maximum pollen tube length (960  μ m) were recorded after 72 H of incubation in caprifigs Assafri and Jrani, respectively. Among the caprifigs studied, four types (Assafri, Jrani, Djebba 1, and Djebba 2) appeared to be suitable pollinators with respect to the criteria investigated.